PHOSPHORUS SOURCES TO FOLIAR FERTILIZATION IN COMMON BEAN CROP - PELÁ, Adilson; RODRIGUES, Marcos Sales; SANTANA, Jaiciclênia da Silva; TEIXEIRA, Itamar Rosa (Scientia Agraria, 2009)
Great part of the phosphorus in the fertilizations tropical soils is lost through fixation. The foliar fertilization, once it uses very lower amounts when compared to the ones applied on soil, it is constituted in an important alternative for the reduction of element losses through fixation in these soils. The objective of this work was to evaluate the applied phosphorus sources to foliar fertilization in commom bean crop, on production components, the grain yield and the amount of the nutrient in the grains. The experiment was carried out in a greenhouse, in pots. The used design was completely randomized with four replications and six treatments: 1- soil fertilization; 2-control treatment (without fertilization); foliar fertilization with the sources 3- potassium phosphite; 4-phosphoric acid; 5-monoammonium phosphate; and 6-potassium phosphate. The P foliar applications were accomplished weekly beginning from the seventh day after the emergence. The grain yield with the P foliar application overcame the witness treatment, but it was inferior the fertilization via soil. The sources were not affected the grain yield, but the potassium phosphate and the monoammonium phosphate provided larger accumulation of P in the grains.